2005
DOI: 10.21236/ada442742
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Modafinil for Vestibular and Aviation-Related Effects

Abstract: REPORT DOCUMENTATION PAGEOMB maintaining the data needed, and completing and reviewing this collection of information, Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Information , 1215 Jefferson Davis Highway, Suite 1204, Arlington, VA 22202-4302. Respondents should be aware that notwithstanding any other provision of law, no person sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For modafinil adverse reactions were primarily headache, dizziness, gastrointestinal complains (e.g. nausea, abdominal pain, dry mouth), increased diuresis, palpitations, nervousness, restlessness, and sleep disturbances and especially in studies with non-sleep deprived individuals, insomnia (Baranski and Pigeau, 1997;Caldwell et al, 1999Caldwell et al, , 2000Caldwell et al, , 2004Dinges et al, 2006;Eddy et al, 2005;Gill et al, 2006;Hart et al, 2006;Lagarde et al, 1995;Pigeau et al, 1995;Wesensten et al, 2002;Whitmore et al, 2006). For methylphenidate a frequently reported side effect (reported in 13 out of 14 trials reporting side effects) was increased heart rate, while increase in blood pressure was not consistently found (Bray et al, 2004;Brumaghim and Klorman, 1998;Clark et al, 1986;Fitzpatrick et al, 1988;Hink et al, 1978;Mehta et al, 2000;Peloquin and Klorman, 1986;Rogers et al, 1999;Strauss et al, 1984;Volkow et al, 1999aVolkow et al, , 1999bWetzel et al, 1981).…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…For modafinil adverse reactions were primarily headache, dizziness, gastrointestinal complains (e.g. nausea, abdominal pain, dry mouth), increased diuresis, palpitations, nervousness, restlessness, and sleep disturbances and especially in studies with non-sleep deprived individuals, insomnia (Baranski and Pigeau, 1997;Caldwell et al, 1999Caldwell et al, , 2000Caldwell et al, , 2004Dinges et al, 2006;Eddy et al, 2005;Gill et al, 2006;Hart et al, 2006;Lagarde et al, 1995;Pigeau et al, 1995;Wesensten et al, 2002;Whitmore et al, 2006). For methylphenidate a frequently reported side effect (reported in 13 out of 14 trials reporting side effects) was increased heart rate, while increase in blood pressure was not consistently found (Bray et al, 2004;Brumaghim and Klorman, 1998;Clark et al, 1986;Fitzpatrick et al, 1988;Hink et al, 1978;Mehta et al, 2000;Peloquin and Klorman, 1986;Rogers et al, 1999;Strauss et al, 1984;Volkow et al, 1999aVolkow et al, , 1999bWetzel et al, 1981).…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…As in the Leduc et al (2009) study, none of the serious modafinil-related side effects (vertigo, dizziness, and nausea; table 1) reported by Caldwell et al were observed in the modafinil group in this study. As highlighted by Leduc et al, several recent studies have suggested that symptoms such as nausea, vertigo and jitteriness seen with modafinil may have been dose dependent (Buguet et al, 2003;Eddy et al, 2005;Wesensten et al, 2002).…”
Section: Mood and Symptoms Questionnairesmentioning
confidence: 99%